Importance of the supraoptimal radiance supply and sunburn effects on apple fruit quality - Racskó, József; Szabó, Zoltán; Nyéki, József (Acta Biologica Szegediensis, 2005)
The aim of this author’s study to research the effect of sunburn on apple fruit quality parameters (skin colour, depth of damaged tissue, fruit flesh firmness, dry matter content). The symptoms of sunburn injury appeared concentric rings shape, differed from together and surface skin colour. This can connect with the ratio of injury. The authors observed the following colours on the fruit surface (from epicentre of blotch on transversal diameter of fruit) dark brown (typical damaged), light brown (moderately damaged), pale red transition (lightly damaged), red surface colour-coverage (not damaged). Sunburn of apple fruits is a surface injury caused by solar radiation, heat and low air relative humidity. That in the initial phase results in a light corky layer, golden or bronze discolouration and injuries of the epidermal tissue, in the surface exposed to radiation. Thus it detracts from its appearance, but in most of the cases it would not cause serious damages in the epidermal tissue. The depth of suffered tissue is not considerable, its values are between 1.5-2.0 mm generally. It is commonly known, that tissue structure of apple fruit is not homogeneous. Accordingly, the degree of injury shows some differences under the different parts of fruit surface. On the basis of the flesh firmness researches, the authors established, that the measure of flesh firmness of suffered part of apple fruit increases under sunburn effect. The consequence of this is the suffered plant cells will die, the water content of this tissue decreases and gets harder. This water-loss caused the increase of soluble solids contant.